Conversation with José María Ezquiaga - Monclús, Javier; Díez, Carmen (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2015)
Good morning, José María. Thank you very much for dedicating your valuable time to us, and for sharing your reflections on this subject we are so interested in. As you know, our research group is undertaking a project under the title of “New Challenges for Spanish Cities: the Legacy of Modern Housing Estates and Options for their Urban Regeneration. Specificities and Similarities with European Models in the Eastern and Western Blocs”. Within this context ZARCH has called this issue Modernist Mass Housing Legacy. When we talk about ‘legacy’ we are using it in the broadest sense of the word, covering conceptual approaches of the ‘first modernity’ and the Athens Charter applied from the outset of these housing estates (also considering the specificities of the moment when they were built and the models they followed). We also take into account the very important reality of the built inheritance, where we must keep in mind the processes of obsolescence many of them are undergoing, and the urban opportunities and possibilities of regeneration, renovation or, sometimes, demolition.